Development of Underhand Volleyball Passing Game Model for Female Students of Class X Vocational High School - Teguh Eko Suprastiyo; Abdul Rachman Syam Tuasikal; Taufiq Hidayat (Jurnal Pendidikan Jasmani (JPJ), 2026)
PJOK learning on volleyball material, especially underhand passing skills, is still dominated by conventional approaches which have an impact on the low learning motivation of female students. This study aims to develop a feasible, practical, and effective underhand passing volleyball game model for female students of class X Vocational High School (SMK). Analysis, design, development, implementation, and evaluation are all elements of the ADDIE model with the research and development (R&D) method. The research involved female students of class X from one of the vocational high schools in Mojokerto City. Data were collected through expert and practitioner validation questionnaires and learning motivation questionnaires. The research results showed a feasibility level of 93.18% from expert validators and 95.45% from practitioner validators, categorized as very feasible. The product's effectiveness was shown by an average learning motivation score of 137.52 out of an ideal score of 175, categorized as effective. The developed game model was declared feasible and effective for the learning motivation of female students in PJOK (Physical Education, Sports, and Health) learning.